2022
DOI: 10.55822/asd.v14i2.229
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Efesiensi Biaya Bahan Baku Dan Biaya Tenaga Kerja Terhadap Volume Produksi Pada Cv “ Jati Jaya ” Singaraja

Abstract: Penelitian ini bertujuan untuk mengetahui pengaruh Biaya Bahan Baku dan Biaya Tenaga Kerja Terhadap Volume Produksi secara parsial maupun simultan pada CV Jati Jaya Singaraja  Periode 2016-2020.Metode Penelitian yang digunakan dalam penelitian ini adalah metode penelitian deskriptif dan verifikatif dengan menggunakan pendekatan kuantitatif. Adapun populasi penelitian ini yaitu laporan keuangan tahunan CV Jati Jaya  serta sampel diambil selama 5 tahun periode 2016-2020. Hasil Penelitian ini menunjukkan ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The period for classifying production volume can be in the form of time units, namely months, quarters, semesters, or annually according to the provisions of the accounting division in a company. Production volume is the total quantity of finished products, which is the result of the collaboration of raw material costs, direct labor costs, and factory overhead costs (Maulida & Tholibin, 2021;Trisnadewi, 2022). A study of Badriah (2016) revealed that the volume of clean water in cubic meters (m 3 ) that can be produced by PDAM (Regional Water Supply Company) at a certain time is also called production volume.…”
Section: Production Volumementioning
confidence: 99%
See 1 more Smart Citation
“…The period for classifying production volume can be in the form of time units, namely months, quarters, semesters, or annually according to the provisions of the accounting division in a company. Production volume is the total quantity of finished products, which is the result of the collaboration of raw material costs, direct labor costs, and factory overhead costs (Maulida & Tholibin, 2021;Trisnadewi, 2022). A study of Badriah (2016) revealed that the volume of clean water in cubic meters (m 3 ) that can be produced by PDAM (Regional Water Supply Company) at a certain time is also called production volume.…”
Section: Production Volumementioning
confidence: 99%
“…A study of Badriah (2016) revealed that the volume of clean water in cubic meters (m 3 ) that can be produced by PDAM (Regional Water Supply Company) at a certain time is also called production volume. Research of Trisnadewi (2022) states that the unit of production volume is a unit of furniture that has been successfully made. While research by Safuan (2017) further broadens the scope of production volume which is not only limited to visible products but the quantity of services provided by service providers is also called production volume such as the number or quantity of container loading and unloading services at the port in an annual period.…”
Section: Production Volumementioning
confidence: 99%
“…Pada zaman globalisasi yang sudah semakin maju dan dunia perdagangan yang semakin kompetitif ini, mengharuskan pedagang agar mampu membuat strategi yang mengutamakan kepuasan konsumen [1] [2]. Agar dapat bertahan dalam persaingan ini, pedagang harus memanfaatkan dengan baik segala sumber daya yang dimilikinya dan menentukan strategi harga yang efektif, karena penetapan harga mempengaruhi minat konsumen untuk membeli produk yang ditawarkan sehingga dapat mempengaruhi volume penjualan pedagang [3] [4].…”
Section: Pendahuluanunclassified